Immune System (Pogo Books: Amazing Body Systems) - Kenny,karen; Kenny,karen (Library Binding Jump!, 2017)
In this book, early fluent readers will explore the role of the immune system in a healthy, functioning body. Vibrant, full-color photos and carefully leveled text will engage young readers as they learn more about the amazing world inside themselves. An infographic illustrates the location of the immune system within the body, and an activity offers readers an opportunity to extend discovery. Children can learn more about the immune system using our safe search engine that provides relevant, age-appropriate websites. Immune System also features reading tips for teachers and parents, a table of contents, a glossary, and an index. Immune System is part of Jump!$1 (Bs Amazing Body Systems series.s
Grade 2 - Grade 5